2012
DOI: 10.1038/nature11151
|View full text |Cite
|
Sign up to set email alerts
|

Attractive and repulsive Fermi polarons in two dimensions

Abstract: The dynamics of a single impurity in an environment is a fundamental problem in many-body physics. In the solid state, a well known case is an impurity coupled to a bosonic bath (such as lattice vibrations); the impurity and its accompanying lattice distortion form a new entity, a polaron. This quasiparticle plays an important role in the spectral function of high-transition-temperature superconductors, as well as in colossal magnetoresistance in manganites. For impurities in a fermionic bath, studies have con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
552
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(578 citation statements)
references
References 38 publications
25
552
1
Order By: Relevance
“…This should enable the Ramsey and spin-echo-type experiments that reveal the OC. Furthermore, experiments with strongly imbalanced Fermi-Fermi mixtures, which addressed the polaron dynamics (mobile impurities) [44,[46][47][48][49], demonstrated that the impurity-host atom interactions can be tuned in the full interaction range, from the strong-attractive to the strong-repulsive regime. This should allow for the exploration of different regimes of the OC, discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should enable the Ramsey and spin-echo-type experiments that reveal the OC. Furthermore, experiments with strongly imbalanced Fermi-Fermi mixtures, which addressed the polaron dynamics (mobile impurities) [44,[46][47][48][49], demonstrated that the impurity-host atom interactions can be tuned in the full interaction range, from the strong-attractive to the strong-repulsive regime. This should allow for the exploration of different regimes of the OC, discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis below, we will present all results in terms of the scattering length a. Importantly, the strength of interactions between host atoms and a given hyperfine state of the impurities can be controlled by tuning the magnetic field [44,[46][47][48][49]. We consider a regime where the density of the impurity atoms is so low that scattering processes taking place on different impurities can be analyzed separately.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is a manifestation of the universal two-body "contact" physics studied by Tan [52,53], and is a recurring feature of rf studies in ultracold atoms [54][55][56][57][58]. We also discuss the "direct" rf protocol [15], in which impurities initially in the |↓ state interact with the bosons, and are transferred to a noninteracting |↑ state. Our discussion can also be extended to the case where both internal states of the impurity are interacting, but with different interaction strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Pertinently, rf spectroscopy can directly probe the spectral properties of quantum impurities [12,15,16,47,48], and has prompted theoretical investigations of impurity spectral functions [34,35,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…12 for fermionic atoms. The quantum simulation of a 2D Fermi system may provide new insight in, e.g., high-T c superconductors.…”
Section: Introductionmentioning
confidence: 99%